Governos subnacionais e a Política de Mudanças Climáticas de São Paulo: uma análise a partir da multiposição dos atores na cidade de São Paulo - Guilherme Barbosa Checco; Eduardo de Lima Caldas (Confins)
São Paulo, with its population and economic dynamics, is a local actor with dimensions and importance that overcome its territory. Thus, climate change mitigation and adaptation policies initiatives in São Paulo can gain significance throughout the country. Attention is drawn to the role played by the city of São Paulo in terms of climate policies from the implementation of a set of public action instruments from 2001 to 2012, including the enactment of its own climate change policy in June 2009, even before the existence of a national and state policy in this agenda. The articulation of the city with different networks and forums also contributed to this process, as well as the influence of the international context. Thus, this article intends to identify the elements that helped the development of this climate leadership by the city of São Paulo.